2004
DOI: 10.1097/00000542-200404000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Antiallodynic Effects of Systemic and Intrathecal Morphine in the Spared Nerve Injury Model of Neuropathic Pain in Rats

Abstract: (1) SNI-induced mechanical allodynia is characterized by a lower paw withdrawal threshold in hairy versus glabrous skin; (2) systemic and intrathecal morphine reverse SNI-induced mechanical allodynia in a dose-dependent fashion; and (3) intrathecal morphine also reverses SNL-induced mechanical allodynia. These results suggest that intrathecal opioids are likely to be effective in the treatment of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Zhao et al (35) reported that i.t. morphine administration is likely to be more effective than s.c. injection in the treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (35) reported that i.t. morphine administration is likely to be more effective than s.c. injection in the treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…*po0.05, **po0.01, ***po0.001 vs sham group. Zhao et al, 2004). Additionally, it has been reported that i.t.…”
Section: Inhibition Of Morphine-or Oxycodone-induced Place Preferencementioning
confidence: 99%
“…125 However, in electrophysiological studies, systemic morphine was less effective than morphine administered via direct spinal application in the inhibition of C-fiber, heat, and mechanical stimulation-evoked activity in dorsal horn neurons 128 and intrathecal administration of morphine has been shown to be effective in reversing mechanical allodynia. 129 Intrathecal ␣2 agonists reverse SNL-induced mechanical allodynia. 130 This is substantiated by recent work indicating that intrathecal ␣2 agonists exacerbate thermal hyperalgesia after SNL.…”
Section: Sciatic Nerve Ligationmentioning
confidence: 99%
“…19 The mechanical allodynia is more prominent in hairy skin. 129 Strain differences influence the extent of the pain behavior (Lewis rats are least affected), but all strains exhibit mechanical sensitivity. 134 Late sprouting of sympathetic fibers into the DRG is documented at 8 weeks post-injury, resulting in basket structures around the neuronal stomata.…”
Section: Sciatic Nerve Ligationmentioning
confidence: 99%
See 1 more Smart Citation